Rein tension in harness trotters during on-track exercise - Egenvall, Agneta; Byström, Anna; Pökelmann, Mette; Connysson, Malin; Kienapfel-Henseleit, Kathrin; Karlsteen, Magnus; McGreevy, Paul; Hartmann, Elke (Frontiers in Veterinary Science, 2022)
Horseracing is under public scrutiny with increasing demands to safeguard horse welfare. It is accepted that, as a result of bit pressure and/or equipment, mouth lesions accompany many types of horse use, including racing. However, there are currently no data available on the range of bit pressures in driven trotters. Our aim was to investigate whether rein tension (RT, proxy for bit pressures) differs among gaits, between tempo within gait, between horses and drivers, and between left/right reins. Standardbreds (n=9), driven by experienced drivers (n=11), performed exercise tests on a racetrack (cross-over design; total 31 tests, data available from 26 tests). Horses’ motion symmetry was measured before tests (trotting in hand). Rein tension, speed and heart rate were measured during exercise. A moving-window filter was applied to RT raw data. Median, maximum and interquartile range for the estimated stride median RT were determined for each rein (left/right) and segment: walk; circling in slow trot followed by transition to faster trot; fast (racing) trot; and slowing down to walk. Mixed models were used for statistical analysis. Least square means for segment median RT ranged between 17-19 N in walk, 34-40 N during circling-accelerating, 51-62 N in fast trot, and 53-71 N for slowing down. Segment maximum RT was between 60-81 N in walk, 104-106 N during circling-accelerating, 72-86 N in fast trot, and 86-129 N during slowing down. Interquartile ranges were between 7-9 N in walk, 28-31 N during circling-accelerating, 8-10 N in fast trot, and 12-18 N for slowing down. Hind limb asymmetry exceeded the recommended threshold in three horses and was associated with higher median (48 N) and maximum (106 N) RT than symmetric horses (29 N and 73 N, respectively, p<0.01). Consistent left-right asymmetry in RT was more common among horses than among drivers. Rein tension increased with increasing heart rate (p≤0.0006). Rein tensions were higher than those reported during riding or in horses worked from the ground. The findings of high RT, taken together with the high reported prevalence of oral injuries in harness trotters, call for further research into RT, motion symmetry and use of equipment.